Focus prosody in Fijian: in-situ focus marking - Mut, Summer; Simard, Candide; Tamata, Apolonia; Lee, Albert (Frontiers in Language Sciences, 2026)
In this paper we investigated the prosodic focus markers of Fijian, an understudied language in the focus prosody literature. Fijian is a verb-initial language in which narrow focus is typically marked by syntactic means (i.e., fronting), making prosodic cues to focus harder to identify. We tested 10 native speakers of Fijian, and elicited in-situ corrective focus by asking them to confirm the correct item sequences. The results showed that regardless of focus location, there is a general elevation of fundamental frequency (F0) and intensity compared with neutral focus, like in Tagalog–another verb-initial language. We argue that, in addition to fronting, Fijian uses F0 and intensity to mark focus.